PERLINDUNGAN HAK MASYARAKAT HUKUM ADAT MELALUI PERATURAN DAERAH DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Nurwahidah, Nurwahidah; Asni, Asni (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The diversity of tribes, religions, customs, and cultures has become a national identity that must be protected by the government, so that minority communities, including Indigenous Peoples, no longer experience discrimination. This research is intended to find out how efforts to protect the Ammatoa Kajang Indigenous Law Community of Bulukumba Regency through Regional Regulation Number 9 of 2015 in the perspective of siyasah syar'iyyah. This research is a field research with a statutory, sociological and syar'i approach. Based on the results of the study, it is known that Regional Regulation Number 9 of 2015 has become a formal legality for the existence of the Ammatoa Kajang Customary Law Community, as well as being the basis for changing the status of protected forest areas to customary forests that have been managed based on pasang ri Kajang. The protection and recognition regulated in Regional Regulation Number 9 of 2015 has provided benefits to the Ammatoa Kajang Indigenous Law Community, so that its existence is in line with the main principles of the concept of siysasah syar'iyyah.